Comparation of combination between enamel matrix derivative (EMD) with synthetic bone graft and EMD with natural bone graft in intrabony defect treatment - Patimah; Arni Irawaty Djais; Mardiana Andi Adam (Makassar Dental Journal, 2020)
Objective: To compare the clinical outcome of combination between EMD with synthetic bone graft and EMD with natural bone graft in intrabony defect treatment. Methods: Online searches have been conducted on the PubMed and Wiley website January 2009-November 2018 using the keywords "reconstructive surgical" AND "chronic periodontitis" AND "regeneration" and the keywords contained in the MeSH browser, produce 272 articles but only six articles met inclusion criteria. Result: At the six studies consisting of 119 subjects showed a decrease in probing depth (PD) and changes in clinical attachment loss (CAL) but not in gingival recession (REC), which one the combination of EMD with natural bone graft has greater than the synthetic bone graft. Conclusion: The combination of EMD with natural bone graft has more changes in PD and CAL com-pared to EMD with synthetic bone graft.